Model Bimbingan Kelompok Teknik Draw a Bridge dalam Meningkatkan Motivasi Belajar - Riva Damayanti; Zainal Fauzi; Akhmad Rizkhi Ridhani (Program Studi Bimbingan dan Konseling FKIP Universitas Islam Jember, 2020)
Based on the results of the pre-research, the researcher got the results, namely the lack of student motivation. To help increase students' motivation to learn, there are various ways, one of which is by using group guidance services. Group guidance services can be used with a variety of methods/techniques. One of them is the draw a bridge technique. The method in this research is R&D with steps of preliminary development, development, expert testing, and lastly revision. The results of expert validation show that this model is feasible and the results of the practitioner's validation of this model can be used in the field. Keywords : Group Guidance, Student Motivation, Draw a Bridge